1996
DOI: 10.1002/(sici)1096-9861(19960212)365:3<479::aid-cne10>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Structural plasticity of identified glomeruli in the antennal lobes of the adult worker honey bee

Abstract: Adult worker honey bees alter their behaviour with age but retain a strong reliance on sensory information from the antennae. The antennae house a diverse array of receptors, including mechanoreceptors, hygroreceptors, olfactory receptors, and contact chemoreceptors, which relay information to the brain. Antennal sensory neurons that project to the antennal lobes of the brain converge onto second-order interneurones to form discrete spheres of neuropil, called glomeruli. The spatial organisation of glomeruli i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(92 citation statements)
references
References 71 publications
4
88
0
Order By: Relevance
“…Perhaps it is because workers spend their younger days in the well-protected and environmentally stable core of the hive. The rising curve also matches the age-dependent development of antenna sensitivity (Robinson, 1987), the volume increase of the glomerular neuropile (Winnington et al, 1996), and the development of mitochondria in flight muscles (unpublished data). This pattern may reflect the change in blood JH titer, which also rises with age (Sasagawa and Kuwahara, 1988;Robinson, 1992).…”
Section: Ontogenic Development Of Learning Capability In Worker and Dsupporting
confidence: 60%
See 1 more Smart Citation
“…Perhaps it is because workers spend their younger days in the well-protected and environmentally stable core of the hive. The rising curve also matches the age-dependent development of antenna sensitivity (Robinson, 1987), the volume increase of the glomerular neuropile (Winnington et al, 1996), and the development of mitochondria in flight muscles (unpublished data). This pattern may reflect the change in blood JH titer, which also rises with age (Sasagawa and Kuwahara, 1988;Robinson, 1992).…”
Section: Ontogenic Development Of Learning Capability In Worker and Dsupporting
confidence: 60%
“…So, when and how is the learning ability acquired-is it developed endogenously or it is developed in response to sensory inputs? Coss et al (1980) noted that the dendritic spines in the calycal interneurons in the mushroom body are different between young and old foragers, and recent works (Gascuel and Masson, 1987;Withers et al, 1993Withers et al, , 1995Durst et al, 1994;Farhbach and Robinson, 1996;Winnington et al, 1996;Fahrbach et al, 1997;Sigg et al, 1997;Morgan et al, 1998) noted the change in the volume of the mushroom body depending on age and foraging experience. However, the relationship between flight experience and such morphological change is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Daly et al (2004) have recently shown that olfactory conditioning is combined with a restructuring of electrical odor response patterns in the AL. Work on adult neuronal plasticity in the honeybee has demonstrated that increases in adult glomerular volume are activity-dependent and correlated with better learning performance (Winnington et al 1996;Sigg et al 1997). Quantitative electron-microscopic studies have lead to the suggestion that volume increase and synapse number changes are independent processes that both contribute to structural plasticity in the AL, although synapse reorganization might only play a minor role on neuropilar volume (Brown et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Olfactory glomeruli are plastic structures undergoing volume changes even during adulthood, depending on previous experience (Drosophila: Devaud et al [2001, 2003; Sachse et al [2007]; Apis : Winnington et al [1996]; Sigg et al [1997]). The latter studies showed significant volume changes in glomeruli after foraging experience, although the bees' actual activity during foraging was not controlled.…”
Section: Changes In Glomerular Volume As a Possible Memory Tracementioning
confidence: 99%